Note on a Hoard of Coins found at Auchenbart, in the Parish of Galston, Aryshire (Proceedings of the Society of Antiquaries of Scotland, 1923)
A small earthenware jug contained a minimum of 228 coins. The hoard is of interest as none of the coins were Scottish: seven were pennies of Edward I of England and the remainder were foreign, mainly from the Low Countries. The probable date of burial of the hoard is AD 1300.